2020
DOI: 10.1002/ncp.10480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enteral Feeding on Vasoactive Support in Septic Shock: A Retrospective Observational Study

Abstract: Background: Introducing enteral nutrition (EN) during hemodynamic instability may induce the splanchnic steal phenomenon, which may worsen systemic oxygen delivery and increase vasopressor dose. We aimed to determine the change in vasopressor dose in septic shock patients who received concomitant EN. We hypothesize that EN delivery is not associated with worsening hemodynamic instability, as defined by an increase in vasopressor dose ≥50% at 24 hours. Methods: This is a retrospective observational cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
(51 reference statements)
0
7
0
8
Order By: Relevance
“…Given the negative effects of epinephrine on splanchnic perfusion and GI motility, 72 patients requiring significant doses of epinephrine vs norepinephrine may experience more EN‐related intolerance and complications. Patients with septic shock who were administered only norepinephrine 73,74 had significantly greater EN tolerance than our pre‐HRNSP group, which only used epinephrine. This may be due to the variances in splanchnic receptor properties between these two agents.…”
Section: Discussionmentioning
confidence: 72%
“…Given the negative effects of epinephrine on splanchnic perfusion and GI motility, 72 patients requiring significant doses of epinephrine vs norepinephrine may experience more EN‐related intolerance and complications. Patients with septic shock who were administered only norepinephrine 73,74 had significantly greater EN tolerance than our pre‐HRNSP group, which only used epinephrine. This may be due to the variances in splanchnic receptor properties between these two agents.…”
Section: Discussionmentioning
confidence: 72%
“…Current literature indicates conflicting results regarding the feasibility and safety of EN in patients with shock. Previous studies showed that the safety cut-off value of EN was likely to be less than 0.3 µg/kg/min in these patients [6][7][8][9][10][11][12][13][14]16]. NUTRIREA-2 study, a large multicenter randomized controlled trial, reported that early EN with 0.56 µg/kg/min norepinephrine infusion was associated with an increased risk of gastrointestinal adverse events in the patients with shock [26].…”
Section: Introductionmentioning
confidence: 95%
“…Numerous studies have demonstrated the feasibility and safety of EN in patients with shock; however, in clinical practices, the management of EN in these patients is still a difficult task [6][7][8][9][10][11][12][13][14][15][16]. Current guidelines offer vague and inconsistent recommendations [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Second, 0 (of 269) patients developed NOBN. One retrospective study evaluating the change in vasopressor dose after EN initiation in patients with septic shock did not find a significant difference in the change in NE dose in patients receiving trophic or full‐dose EN 35 …”
Section: What Is the Clinical Evidence For Initiating En In Septic Shock?mentioning
confidence: 99%
“…One retrospective study evaluating the change in vasopressor dose after EN initiation in patients with septic shock did not find a significant difference in the change in NE dose in patients receiving trophic or full-dose EN. 35 Since 2011, seven RCTs with at least one EN arm have enrolled patients with circulatory shock. 22,23,[36][37][38][39][40] Two of seven trials (REDOX and NUTRIREA-2) had circulatory shock as an inclusion criteria, and nonocclusive mesenteric ischemia occurred in 0.3% and 2% in those receivingEN, respectively.…”
Section: What Is the Clinical Evidence For Initiating En In Septic Shock?mentioning
confidence: 99%